Revisiting the DBM-Tree - Vieira, Marcos R.; Chino, Fabio J. T.; Traina, Agma J. M.; Traina Jr., Caetano (Journal of Information and Data Management, 2010)
In this article we revisit the DBM-tree as well as the following up research projects related to the DBM-tree.